Flexible glass multi-step fine strengthening method and flexible strengthened glass

Through the multi -step alternating heating and mild ion exchange processing, the problem of strengthening the super -thin and flexible glass reinforcement is solved, and the mechanical performance and surface compression of the glass are achieved efficiently.

CN119371089APending Publication Date: 2025-01-28WUHAN UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411480165.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the problem that ultra-thin flexible glass is prone to break after surface scratches or wears, and the traditional one-step ion exchange chemical strengthening method cannot achieve the ideal surface compressive stress and stress layer depth at the same time.

Method used

Adopting multi -step and fine reinforcement methods, circulating alternate heating and insulation processing and ion exchange treatment. By adjusting temperature, time, and salt formula formula to gradually increase the pressure stress and stress layer depth of the glass surface.

Benefits of technology

The efficient reinforcement of flexible glass has been achieved, and its extreme bending radius, surface hardness and surface compression stress are enhanced. At the same time, the depth and internal tension stress of the stress layer are controlled to avoid the adverse effects of structure relaxation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a flexible glass multi-step fine strengthening method and flexible strengthened glass. The method comprises the following steps: firstly, preheating flexible glass which is cleaned and dried in advance to 400-600 DEG C, keeping the temperature for a period of time, and then immersing the flexible glass into fused salt A for first ion exchange treatment; taking out the glass, keeping the temperature at 200-400 DEG C for a period of time, and immersing the glass into molten salt B for secondary ion exchange treatment; and taking out the glass again, keeping the temperature at 200-400 DEG C for a period of time, immersing the glass into the fused salt C for third ion exchange treatment, taking out the glass, naturally cooling, and cleaning to obtain the flexible tempered glass product with excellent performance. In the whole ion exchange process, potassium, rubidium, cesium and other large-size ions in different fused salts are used for exchanging small-size sodium ions on the surface of the flexible glass, and heat preservation heat treatment of ion exchange gaps is supplemented, so that it is ensured that the flexible tempered glass has high surface compressive stress and low internal tensile stress at the same time; therefore, better mechanical properties are shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of inorganic non-metallic materials and glass processing, and in particular to a flexible glass multi-step fine strengthening method and flexible strengthened glass. Background Art

[0002] The application of ultra-thin flexible glass is increasing in various fields, especially the cover glass of mobile displays such as smartphones and tablets. These glasses will have different degrees of surface scratches and surface wear during daily use. Since the thickness of flexible glass itself is very small (≤100μm), it is easy to break under the influence of surface damage, so it must be strengthened.

[0003] Ion exchange is a common method of chemically strengthening glass and one of the most effective means of improving the mechanical properties of flexible glass. This method mainly toughens the material through ion exchange, using ions with larger diameters in the molten salt to exchange ions with smaller diameters inside the glass, thereby generating a compressive stress layer in the glass, so that cracks on the surface of the glass need to overcome compressive stress when spreading inward, thereby inhibiting the spread of cracks and improving the mechanical properties of the flexible glass, such as bending radius and scratch resistance.

[0004] The most important evaluation parameters of chemically strengthened glass are surface compressive stress (CS) and depth of stress layer (DOL). For the traditional one-step ion exchange chemical strengthening method, DOL increases continuously with the increase of exchange time, but due to structural relaxation, CS will increase first and then decrease with the increase of exchange time. Therefore, when obtaining CS or DOL that meets the application conditions, DOL or CS often cannot reach the ideal value. Although DOL is an effective barrier to prevent microcracks from invading the tensile stress layer, unlike ordinary ultra-thin glass that pursues a large DOL, flexible glass needs to achieve fine control of DOL. This is because the thickness of flexible glass is extremely thin. When DOL increases under a certain CS, the tensile stress (CT) inside the glass will increase rapidly, resulting in stress failure or self-explosion of the flexible glass surface. Therefore, in order to obtain reasonable CS and DOL, while avoiding the influence of excessive CT and structural relaxation, it is more urgent for flexible strengthened glass products to develop a multi-step fine strengthening method. Summary of the invention

[0005] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art and to provide a multi-step fine strengthening method for flexible glass, comprising: cyclically alternating heating and heat preservation treatment and ion exchange treatment of the flexible glass, wherein the number of cycles is 3 times.

[0006] Furthermore, the flexible glass needs to be cleaned and dried before starting the treatment, and after all the treatments are completed, the flexible glass is cooled naturally and then cleaned and dried again.

[0007] Furthermore, the thickness of the flexible glass is ≤0.1 mm.

[0008] Furthermore, in the first cycle, the temperature of the heating and insulation treatment is 400-600°C, preferably 450°C-550°C; the insulation time is 10-60min, preferably 10min-30min; the temperature of the ion exchange treatment is 350-450°C, preferably 350°C-400°C; the ion exchange treatment time is 30-120min, preferably 30min-60min.

[0009] Furthermore, the molten salt formula used in the ion exchange treatment in the first cycle is: 65wt%-99wt% potassium nitrate, 0wt%-0.3wt% potassium hydroxide, 0wt%-3.0wt% potassium carbonate, 0wt%-40wt% rubidium nitrate, 0wt%-40wt% cesium nitrate, totaling 100wt%. The main purpose of the first round of ion exchange treatment is to ensure that the potassium ions in the molten salt are fully exchanged with the sodium ions in the flexible glass. If the molten salt contains rubidium nitrate and cesium nitrate, a certain amount of rubidium ions and cesium ions will be introduced during the ion exchange.

[0010] Preferably, the molten salt formula used in the ion exchange treatment in the first cycle is: 67.9wt%-97.9wt% potassium nitrate, 0wt%-0.1wt% potassium hydroxide, 0wt%-2.0wt% potassium carbonate, 0wt%-20wt% rubidium nitrate, 0wt%-10wt% cesium nitrate, totaling 100wt%.

[0011] Furthermore, in the second cycle, the temperature of the heating and heat preservation treatment is 200-400°C, preferably 300°C-350°C; the heat preservation time is 10min-10h, preferably 1h-6h; the temperature of the ion exchange treatment is 350-450°C, preferably 380°C-450°C; the ion exchange treatment time is 30-120min, preferably 30min-60min. At this time, the role of the cyclic heat preservation is to ensure that the potassium ions, rubidium ions, and cesium ions introduced into the flexible glass are fully diffused at a temperature lower than the ion exchange treatment temperature, thereby increasing the depth of the stress layer. Since the heat preservation temperature is much lower than the strain point of the flexible glass, the adverse effects of structural relaxation are relatively small. At this time, the heat preservation time and temperature can be changed in combination with the production demand conditions, so as to conveniently and flexibly adjust the depth of the stress layer.

[0012] Furthermore, the molten salt formula used in the ion exchange treatment in the second cycle is: 30wt%-80wt% of potassium nitrate, 0wt%-50wt% of rubidium nitrate, 0wt%-50wt% of cesium nitrate, and a total of 100wt%. The second round of ion exchange treatment is as follows: the ratio of rubidium nitrate and cesium nitrate in the molten salt is increased, and the potassium ions, rubidium ions, and cesium ions therein are not only exchanged with the sodium ions in the flexible glass, but also exchanged with the potassium ions in the flexible glass, thereby increasing the surface compressive stress of the flexible glass.

[0013] Preferably, the molten salt formula used in the ion exchange treatment in the second cycle is: 30wt%-50wt% potassium nitrate, 30wt%-35wt% rubidium nitrate, 25wt%-50wt% cesium nitrate, totaling 100wt%.

[0014] Furthermore, in the third cycle, the temperature of the heating and insulation treatment is 200-400°C, preferably 300°C-350°C; the insulation time is 10min-10h, preferably 30min-3h; the temperature of the ion exchange treatment is 300-400°C, preferably 350°C-380°C; the ion exchange treatment time is 10-60min, preferably 10min-30min.

[0015] Furthermore, the molten salt formula used in the ion exchange treatment in the third cycle is: potassium nitrate 0wt%-50wt%, rubidium nitrate 0wt%-90wt%, cesium nitrate 0wt%-90wt%, totaling 100wt%. The purpose of the third round of ion exchange treatment is to further increase the proportion of rubidium nitrate and cesium nitrate in the molten salt, supplement the potassium ions, rubidium ions, and cesium ions diffused from the surface of the flexible glass to the inside, and further increase the compressive stress on the glass surface.

[0016] Preferably, the molten salt formula used in the ion exchange treatment in the third cycle is: potassium nitrate 0wt%-10wt%, rubidium nitrate 50wt%-90wt%, cesium nitrate 30wt%-90wt%, totaling 100wt%.

[0017] The second object of the present invention is to provide a flexible tempered glass prepared according to the above method, wherein the thickness is ≤0.1 mm, the ultimate bending radius is 6 mm-8.5 mm, the surface hardness is 580 HV-620 HV, the surface compressive stress is greater than 900 MPa, the stress layer depth is 15 μm-22 μm, and the central tensile stress is 204 MPa-370 MPa.

[0018] The present invention selects potassium nitrate, rubidium nitrate, cesium nitrate and the like as ion exchange agents, and performs ion exchange treatment on the flexible glass three times in succession, so that the small-sized sodium ions on the surface of the glass are fully exchanged with the large-sized ions (potassium, rubidium, cesium) in each molten salt, and the field strength and radius of these ions are higher than those of the sodium ions in the glass, and the compressive stress on the surface of the glass can be greatly improved after the ion exchange. In addition, in the transition stage of each step of ion exchange, the flexible glass is placed in air at a relatively low temperature for a period of time, so that it obtains a higher surface compressive stress and controls the depth of the stress layer during the first and second step ion exchange processes, while eliminating the adverse effects of structural relaxation.

[0019] The present invention uses potassium hydroxide as an ion exchange accelerator, which can not only change the surface state of the flexible glass, but also improve the surface activity of the flexible glass and promote the ion exchange reaction. The present invention uses potassium carbonate as an impurity remover, which can react with calcium ions and magnesium ions that hinder ion exchange to generate compounds with high melting points or low solubility, thereby reducing the adverse effects of harmful impurity ions on the ion exchange effect. By reasonably matching the composition of the molten salt and finely controlling the ion exchange process, it is ensured that a larger surface compressive stress and a smaller tensile stress are obtained at the same time, so that the flexible strengthened glass exhibits better mechanical properties.

[0020] Compared with the existing similar processes and products, the progress of the present invention is mainly reflected in the following points: (1) The present invention overcomes the adverse effects of the thin flexible glass through multiple steps of fine heat preservation heat treatment and ion exchange treatment, and realizes the coordination and unification of the surface compressive stress, stress layer depth and internal tensile stress; (2) The process flow of the present invention is simple, the raw materials are cheap and easy to obtain, the reaction vessel required for ion exchange is simple in structure and easy to operate, and meets the conditions of practicality and industrialization; (3) The flexible strengthened glass product prepared according to the method of the present invention has excellent performance. The maximum bending radius of the flexible strengthened glass with a thickness of 100 μm can reach 6.7 mm, the surface hardness value can reach 620 HV, the surface compressive stress value is greater than 1100 MPa, and the stress layer depth is 17 μm. DETAILED DESCRIPTION

[0021] In order to enable those skilled in the art to fully understand the technical solutions and beneficial effects of the present invention, further description is given below in conjunction with specific embodiments.

[0022] The present invention preheats the flexible glass in a cyclic alternating manner and then performs an ion exchange treatment, thereby controlling the depth of the stress layer. The flexible glass is placed at a relatively low temperature for heat preservation in the gap between each step of ion exchange, thereby minimizing the adverse effects of structural relaxation. Introducing larger alkali metal ions such as potassium ions, rubidium ions, and cesium ions into the molten salt effectively adjusts the surface compressive stress. Potassium nitrate, rubidium nitrate, cesium nitrate, etc. are selected as ion exchangers, potassium hydroxide is selected as an ion exchange accelerator, and potassium carbonate is used as an ion exchange impurity remover, further enhancing the effect of chemical strengthening. By adjusting the insulation temperature, insulation time, and ratio of alkali metal ions in the gap between each step of ion exchange, refined control of the surface compressive stress and the depth of the stress layer is achieved, and finally a flexible strengthened glass product with high CS and low CT is obtained, thereby improving the mechanical properties of the flexible glass.

[0023] Comparative Example 1

[0024] The flexible glass is chemically strengthened by the conventional one-step ion exchange method. The specific process is as follows:

[0025] The flexible glass original plate (specification 40*100*0.1mm) is washed with water or ethanol and dried, then the flexible glass is immersed in 380°C pure potassium nitrate molten salt and kept at this temperature for 60 minutes; the flexible glass is taken out and naturally cooled to room temperature, and washed with water or ethanol to obtain flexible strengthened glass.

[0026] Example 1

[0027] The flexible glass original plate (specification 40*100*0.1mm) was washed with water and ethanol and then dried, then preheated to 450°C and kept at this temperature for 30 minutes.

[0028] After the insulation is completed, the flexible glass is immersed in a mixed molten salt A (ingredients: 97.9wt% potassium nitrate, 0.1wt% potassium hydroxide, 2.0wt% potassium carbonate) at 400° C. and is kept at this temperature for 60 minutes.

[0029] The flexible glass was taken out and transferred to a 300° C. environment for 2 h of heat preservation. After the heat preservation was completed, the flexible glass was immersed in molten salt B (composition: 50 wt % potassium nitrate, 50 wt % cesium nitrate) at 380° C. again and kept at this temperature for 60 min.

[0030] The flexible glass was taken out and transferred to a 300° C. environment for 1 hour. After the insulation was completed, the flexible glass was immersed in a 350° C. molten salt C (composition: potassium nitrate 10wt%, cesium nitrate 90wt%) for the third time and was kept at this temperature for 30 minutes.

[0031] Finally, the flexible glass is taken out, cooled naturally to room temperature in the air, and then washed with ultrapure water and ethanol and dried to obtain flexible strengthened glass.

[0032] Example 2

[0033] The flexible glass original plate (specification 40*100*0.1mm) was washed with ultrapure water and ethanol and then dried, then preheated to 450°C and kept at this temperature for 30 minutes.

[0034] After the insulation is completed, the flexible glass is immersed in a mixed molten salt A (ingredients: 97.9wt% potassium nitrate, 0.1wt% potassium hydroxide, 2.0wt% potassium carbonate) at 400° C. and is kept at this temperature for 60 minutes.

[0035] The flexible glass was taken out and transferred to a 300° C. environment for 3 hours of heat preservation. After the heat preservation was completed, the flexible glass was immersed in molten salt B (composition: 50 wt% potassium nitrate, 50 wt% rubidium nitrate) at 380° C. again and kept at this temperature for 60 minutes.

[0036] The flexible glass was taken out and transferred to a 300° C. environment for 1 hour. After the insulation was completed, the flexible glass was immersed in a 350° C. molten salt C (composition: potassium nitrate 10wt%, rubidium nitrate 90wt%) for the third time and kept at this temperature for 30 minutes.

[0037] Finally, the flexible glass is taken out, cooled naturally to room temperature in the air, and then washed with ultrapure water and ethanol and dried to obtain flexible strengthened glass.

[0038] Example 3

[0039] The flexible glass original plate (specification 40*100*0.1mm) was washed with ultrapure water and ethanol and then dried, then preheated to 500°C and kept at this temperature for 20 minutes.

[0040] After the insulation is completed, the flexible glass is immersed in a mixed molten salt A (ingredients: 97.9wt% potassium nitrate, 0.1wt% potassium hydroxide, 2.0wt% potassium carbonate) at 380° C. and is kept at this temperature for 30 minutes.

[0041] The flexible glass was taken out and transferred to a 350°C environment for 1 hour. After the insulation was completed, the flexible glass was immersed in molten salt B (composition: 30 wt% potassium nitrate, 35 wt% rubidium nitrate, 35 wt% cesium nitrate) at 380°C again and kept at this temperature for 30 minutes.

[0042] The flexible glass was taken out and transferred to a 350° C. environment for 30 minutes. After the insulation was completed, the flexible glass was immersed in a 380° C. molten salt C (composition: 50 wt % rubidium nitrate, 50 wt % cesium nitrate) for the third time and kept at this temperature for 30 minutes.

[0043] Finally, the flexible glass is taken out, cooled naturally to room temperature in the air, and then washed with ultrapure water and ethanol and dried to obtain flexible strengthened glass.

[0044] Example 4

[0045] The flexible glass original plate (specification 40*100*0.1mm) was washed with ultrapure water and ethanol and then dried, then preheated to 550°C and kept at this temperature for 10 minutes.

[0046] After the insulation is completed, the flexible glass is immersed in a mixed molten salt A (ingredients: 67.9wt% potassium nitrate, 20wt% rubidium nitrate, 10wt% cesium nitrate, 0.1wt% potassium hydroxide, 2.0wt% potassium carbonate) at 380° C. and is kept at this temperature for 30 minutes.

[0047] The flexible glass was taken out and transferred to a 300°C environment for 10 minutes. After the insulation was completed, the flexible glass was immersed in molten salt B (composition: 50 wt% potassium nitrate, 30 wt% rubidium nitrate, 20 wt% cesium nitrate) at 380°C again and kept at this temperature for 20 minutes.

[0048] The flexible glass was taken out and transferred to a 300°C environment for 10 minutes. After the insulation was completed, the flexible glass was immersed in a 350°C molten salt C (composition: 10 wt% potassium nitrate, 60 wt% rubidium nitrate, 30 wt% cesium nitrate) for the third time and kept at this temperature for 10 minutes.

[0049] Finally, the flexible glass is taken out, cooled naturally to room temperature in the air, and then washed with ultrapure water and ethanol and dried to obtain flexible strengthened glass.

[0050] In order to fully understand the performance of the flexible tempered glass products obtained in Comparative Example 1 and Examples 1-4, we took samples and conducted a series of tests:

[0051] The two-point bending method was used to test the ultimate bending radius of flexible tempered glass. The specific process is as follows: a flexible glass sample is placed between two parallel plates, with both ends of the sample contacting baffles, one of which is fixed and the other moves. As the moving baffle moves toward the middle at a speed of 2 mm / s, the sample gradually bends and deforms until it breaks. The ultimate bending radius of the sample can be measured based on the distance between the two plates when the glass breaks.

[0052] The Vickers hardness of the flexible tempered glass sample was measured using a Vickers hardness tester combined with the indentation method. A diamond regular pyramid indenter was used to press into the surface of the test sample under a specified load. After a certain period of time, the load was removed and the diagonal length of the indentation was measured to calculate the Vickers hardness.

[0053] The FSM tempered glass surface stress meter is used to measure the surface compressive stress, stress layer depth and corresponding central tensile stress of the sample. After chemical strengthening, the surface stress of the flexible glass changes. Due to the surface stress, the glass divides the incident light into two mutually perpendicular polarized light beams. This phenomenon is called the photoelastic effect. The stress magnitude and stress layer depth of the surface of the strengthened flexible glass can be calculated by the number and spacing of the interference fringes formed by the two beams of light.

[0054] The test results are shown in Table 1 below.

[0055] Table 1 Performance comparison of different flexible tempered glass products

[0056]

[0057] As can be seen from the above table, compared with Comparative Example 1, Examples 1-4 can finely adjust the surface compressive stress and stress layer depth of the glass by adjusting the molten salt composition and ion exchange, preheating, and holding temperature and time parameters while ensuring that the Vickers hardness of the flexible glass is not reduced, so that the limit bending radius of the flexible glass is improved to varying degrees, and the adverse effects of structural relaxation can be reduced by adjusting the holding temperature and holding time. In short, the present invention can flexibly adjust the ion exchange system according to product performance requirements and product size conditions to obtain chemically strengthened flexible glass with better performance.

Claims

1. A multi-step fine strengthening method for flexible glass, characterized in that The method comprises: performing heating and heat preservation treatment and ion exchange treatment on the flexible glass in a cyclic alternating manner, wherein the number of cyclic alternations is 3 times.

2. The method according to claim 1, characterized in that: The flexible glass needs to be cleaned and dried before starting the treatment. After all the treatments are completed, the flexible glass is naturally cooled and cleaned and dried again. The thickness of the flexible glass is ≤0.1 mm.

3. The method according to claim 1, characterized in that: In the first cycle, the temperature of the heating and heat preservation treatment is 400-600° C., the heat preservation time is 10-60 minutes, the temperature of the ion exchange treatment is 350-450° C., and the ion exchange treatment time is 30-120 minutes.

4. The method according to claim 3, characterized in that: The molten salt formula used in the ion exchange treatment in the first cycle is: 65wt%-99wt% potassium nitrate, 0wt%-0.3wt% potassium hydroxide, 0wt%-3.0wt% potassium carbonate, 0wt%-40wt% rubidium nitrate, 0wt%-40wt% cesium nitrate, totaling 100wt%.

5. The method according to claim 1, characterized in that: In the second cycle, the temperature of the heating and heat preservation treatment is 200-400°C, the heat preservation time is 10min-10h, the temperature of the ion exchange treatment is 350-450°C, and the ion exchange treatment time is 30-120min.

6. The method according to claim 5, characterized in that: The molten salt formula used in the ion exchange treatment in the second cycle is: 30wt%-80wt% potassium nitrate, 0wt%-50wt% rubidium nitrate, 0wt%-50wt% cesium nitrate, totaling 100wt%.

7. The method according to claim 1, characterized in that: In the third cycle, the temperature of the heating and heat preservation treatment is 200-400°C, the heat preservation time is 10min-10h, the temperature of the ion exchange treatment is 300-400°C, and the ion exchange treatment time is 10-60min.

8. The method according to claim 7, characterized in that: The molten salt formula used in the ion exchange treatment in the third cycle is: potassium nitrate 0wt%-50wt%, rubidium nitrate 0wt%-90wt%, cesium nitrate 0wt%-90wt%, totaling 100wt%.

9. A flexible tempered glass, characterized in that: The flexible strengthened glass is prepared according to any one of the methods of claims 1-8.

10. The flexible tempered glass according to claim 9, wherein: The thickness of the flexible tempered glass is ≤0.1mm, the ultimate bending radius is 6mm-8.5mm, the surface hardness value is 580HV-620HV, the surface compressive stress value is >900MPa, the stress layer depth is 15μm-22μm, and the central tensile stress is 214MPa-370MPa.

Citation Information

Patent Citations

  • Cesium-rubidium-potassium monolithic flameproof glass and preparation method

    CN102503178A

  • Method for producing tempered glass with plurality of surface stress layers and tempered glass product

    CN102815860A

  • Chemical enhancement method of high-alkali aluminosilicate glass

    CN107572839A

  • Method for improving impact resistance performance of thin high-alkali-content alumina silicate glass

    CN107673632A

  • Application of single-step or multi-step reinforcing method in preparing glass ceramic applied to 5G communication mobile terminal

    CN108658477A